Truncated titin proteins and titin haploinsufficiency are targets for functional recovery in human cardiomyopathy due to TTN mutations - Fomin, Andrey; Gaertner, Anna; Cyganek, Lukas; Tiburcy, Malte; Tuleta, Izabela; Wellers, Luisa; Folsche, Lina; Hobbach, Anastasia J.; Von Frieling-Salewsky, Marion; Unger, Andreas; Hucke, Anna; Koser, Franziska; et al. (Science Translational Medicine, 2021)
Heterozygous truncating variants in TTN (TTNtv), the gene coding for titin, cause dilated cardiomyopathy (DCM), but the underlying pathomechanisms are unclear and disease management remains uncertain. Truncated titin proteins have not yet been considered as a contributor to disease development. Here, we studied myocardial tissues from nonfailing donor hearts and 113 patients with end-stage DCM for titin expression and identified a TTNtv in 22 patients with DCM (19.5%). We directly demonstrate titin haploinsufficiency in TTNtv-DCM hearts and the absence of compensatory changes in the alternative titin isoform Cronos. Twenty-one TTNtv-DCM hearts in our cohort showed stable expression of truncated titin proteins. Expression was variable, up to half of the total titin protein pool, and negatively correlated with patient age at heart transplantation. Truncated titin proteins were not detected in sarcomeres but were present in intracellular aggregates, with deregulated ubiquitin-dependent protein quality control. We produced human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs), comparing wild-type controls to cells with a patient-derived, prototypical A-band-TTNtv or a CRISPR-Cas9-generated M-band-TTNtv. TTNtv-hiPSC-CMs showed reduced wild-type titin expression and contained truncated titin proteins whose proportion increased upon inhibition of proteasomal activity. In engineered heart muscle generated from hiPSC-CMs, depressed contractility caused by TTNtv could be reversed by correction of the mutation using CRISPR-Cas9, eliminating truncated titin proteins and raising wild-type titin content. Functional improvement also occurred when wild-type titin protein content was increased by proteasome inhibition. Our findings reveal the major pathomechanisms of TTNtv-DCM and can be exploited for new therapies to treat TTNtv-related cardiomyopathies.
CRIS-Team Scopus Importer:2023-03-08